STOCK ASSESSMENT OF SIN CROAKER JOHNIEOPS SINA (CUVIER) FROM BOMBAY WATERS - CHARKABORTY, SUSHANT KUMAR (Journal of Indian Fisheries Association, 2015)
Growth, mortality and stock parameters of Johnieops sina Â·(Cuvier)based on the data collected from 1989 to 1994 from Sassoon Dock andNew Ferry Wharf landing centres of Greater Bombay has been discussedhere. The von Bertallanffy's growth parameters for this species wereestimated as follows, Loo = 266 mm, K = 0.91 per year and Woo= 193 g. Thisspecies grows to 159 and 223 mm at the end of first and second year ofits life. The mortality parameters estimated were Z = 6.17, M = 2/'3 andF = 4.14. TheE and U were calculated as 0.62 and 0.63 respectively. Lengthcohort and Thompson Bell analyses show that there is no decline in thecatches at the present level of fishing. But even by doubling the effortsthe catches can go up by only 9.4 % indicating that the fishing efforts isnot economical and proportional to the increase in yield.